Lithium metal composite negative electrode, preparation method and lithium metal secondary battery
By preparing Li-PAA/LiF or Li-PAA/Li2S double-layer structure surface protective layer on the surface of lithium metal negative electrode, the short life and safety of lithium metal secondary batteries are solved, the stability and safety of battery performance are improved, and the preparation process is simplified.
Patent Information
- Application Number
- CN202411850763.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-11
AI Technical Summary
The lifespan of lithium metal secondary batteries is short and it is easy to form solid electrolyte membranes (SEIs) and lithium dendrites, resulting in battery performance attenuation and safety issues. The existing modification methods are complex in operation and high in cost, and are not suitable for industrial applications.
The surface protective layer with a double-layer structure is prepared on the surface of the lithium metal negative electrode. The outer layer is a Li-PAA polymer layer and the inner layer is a LiF or Li2S layer that is self-generated by lithium metal and fluoride or sulfide under the action of the electrolyte. The protective layer is formed by coating the dispersion of PAA/fluoride or PAA/sulfide and drying of the blower oven, and has good lithium ion transport capability and adaptability.
It effectively suppresses the side reaction between lithium metal and electrolyte, extends the cycle life of lithium metal secondary batteries, improves the stability and safety of the battery, simplifies the preparation process, and reduces costs.
Smart Images

Figure CN119812211A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium metal secondary batteries, and in particular to a lithium metal composite negative electrode, a preparation method and a lithium metal secondary battery. Background Art
[0002] Traditional lithium-ion batteries based on graphite negative electrodes with intercalation storage mechanisms are difficult to meet the needs of long driving range and large carrying capacity. The capacity of lithium metal negative electrodes with a deposition / stripping reaction mechanism is as high as 3860mAh / g, which is much higher than that of graphite negative electrodes. Batteries constructed with lithium metal negative electrodes have a mass energy density of more than 400Wh / kg. However, the life of lithium metal secondary batteries is very short, which limits their application. On the one hand, lithium metal has strong reduction properties and is prone to side reactions with electrolytes to form solid electrolyte membranes (SEI). The SEI membrane has poor elasticity and is difficult to adapt to the volume expansion of the lithium metal negative electrode during the cycle and breaks, resulting in the exposure of new lithium metal surfaces to continue to react with the electrolyte, resulting in battery performance degradation. On the other hand, the uneven deposition of lithium ions on the surface of the lithium metal negative electrode during charging leads to the formation of lithium dendrites, which pierce the diaphragm and cause safety problems for the battery.
[0003] In order to solve the application problem of lithium metal negative electrode, many researchers at home and abroad have modified lithium metal negative electrode and constructed lithium metal secondary batteries. Related research includes magnetron sputtering coating, lithium metal alloying, etc. These modification methods are often complicated to operate, costly, and not conducive to industrial application. It is reported that a layer of polyrotaxane-copolymerized acrylic acid (PR-PAA) polymer with high elasticity and elasticity is coated on the lithium sheet to prepare an artificial SEI layer. The artificial SEI layer has good deformation ability, can resist the stress generated by lithium dendrites, and effectively adapt to the morphological changes caused by volume fluctuations of the lithium negative electrode. However, the polymer coating is relatively slow in sub-transmission relative to inorganic coatings such as lithium fluoride and lithium sulfide, and the Young's modulus is low, and the inhibitory effect on metal lithium dendrites is limited. Patent CN109950476A proposes a relatively simple method to construct the interface layer of the lithium metal negative electrode, which directly hot presses the metal fluoride pole piece with lithium metal to form lithium fluoride on the surface of lithium metal. The electrochemical stability of the lithium metal anode constructed by this method is improved, but its interface layer is a pure inorganic component with strong mechanical brittleness, making it difficult to adapt to the volume change caused by the long-term cycling of the lithium metal anode. Therefore, a lithium metal anode that can adapt to the volume change caused by the long-term cycling of the lithium metal anode, can quickly transport lithium ions, and has a simple preparation process has not yet been developed. Summary of the invention
[0004] In order to solve the above problems, the purpose of the present invention is to provide a lithium metal composite negative electrode. The specific technical solution of the present invention is as follows:
[0005] The present invention provides a lithium metal composite negative electrode, characterized in that it comprises lithium metal and a lithium metal surface protective layer, wherein:
[0006] The lithium metal surface protection layer comprises an outer polymer elastic layer and an inner inorganic lithium-containing compound layer;
[0007] The outer polymer elastic layer is a Li-PAA layer, and the inner inorganic lithium-containing compound layer is a LiF or Li2S layer;
[0008] The inner inorganic lithium-containing compound layer is generated by a self-electrochemical reaction between lithium metal and fluoride or sulfide under the action of an electrolyte.
[0009] The present invention also provides a method for preparing the above-mentioned lithium metal secondary battery, characterized in that it comprises the following steps:
[0010] S1. In a dry air atmosphere, a dispersion of PAA / fluoride or PAA / sulfide is uniformly coated on the surface of lithium metal and dried in a blast oven. The adhesion property of PAA and the spontaneous reaction with lithium metal form a strong Li-PAA elastic protective layer. During the blast drying process, the contact portion of the fluoride or sulfide in the protective layer with the lithium metal undergoes a replacement reaction, a small amount of LiF or Li2S is generated inside the protective layer, and a surface protective layer of an outer Li-PAA layer and an inner small amount of LiF or Li2S layer is initially generated on the surface of the lithium metal, thereby obtaining a Li-PAA / fluoride / Li negative electrode or a Li-PAA / sulfide / Li negative electrode;
[0011] S2, assembling a Li-PAA / fluoride / Li negative electrode or a Li-PAA / sulfide / Li negative electrode and a high-capacity positive electrode into a battery and filling the corresponding electrolyte and then standing;
[0012] S3. Utilize the further spontaneous electrochemical reaction between lithium metal and fluoride or sulfide under the action of electrolyte to completely convert the fluoride or sulfide in the surface protective layer into LiF or Li2S, generate a double-layer surface protective layer with an outer Li-PAA layer and an inner LiF or Li2S layer, and obtain a Li-PAA / LiF / Li negative electrode or a Li-PAA / Li2S / Li negative electrode, that is, a lithium metal composite negative electrode.
[0013] Preferably, the fluoride is any one of carbon fluoride, copper fluoride, magnesium fluoride, silver fluoride, cobalt fluoride and iron fluoride; the sulfide is any one of iron disulfide, copper sulfide, cobalt sulfide and chalcopyrite.
[0014] Preferably, the thickness of the surface protection layer in the lithium metal composite negative electrode is 100 nm-2 μm.
[0015] Preferably, the high-capacity positive electrode is any one of elemental sulfur, sulfided polyacrylonitrile, lithium-rich manganese-based, high-nickel ternary, and lithium cobalt oxide.
[0016] Preferably, the dispersion solvent is N-methylpyrrolidone.
[0017] Preferably, in the dispersion, the concentration of PAA is in the range of 0.1 wt% to 0.8 wt%, and the concentration of fluoride or sulfide is in the range of 0.1 wt% to 10 wt%.
[0018] Preferably, the coating amount of the dispersion on the surface of the lithium metal is in the range of 0.005-0.5 mL / cm 2 .
[0019] Preferably, the operating temperature of the blast oven is 50-80° C.; the standing time is 6-24 hours.
[0020] The present invention also provides a lithium metal secondary battery, characterized in that it comprises a negative electrode, a positive electrode, and an electrolyte, wherein the negative electrode is the above-mentioned lithium metal composite negative electrode or a lithium metal composite negative electrode prepared by the above-mentioned preparation method.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention prepares a surface protective layer with a double-layer structure on the surface of the lithium metal negative electrode, firstly inhibiting the direct contact between the electrolyte and the lithium metal negative electrode, thereby inhibiting the occurrence of side reactions; in addition, the outer Li-PAA layer in the lithium metal surface protective layer can not only transmit lithium ions, but also adapt to the volume expansion of lithium metal during the charging and discharging process, thereby ensuring the stability of the negative electrode interface; the inner LiF or Li2S layer in the lithium metal surface protective layer is evenly distributed and has a high lithium ion transmission rate, and the dense protective layer formed by it can optimize the transmission of lithium ions and inhibit the formation of lithium dendrites;
[0023] (2) The lithium metal composite negative electrode preparation method provided by the present invention adjusts the thickness of the protective layer on the surface of the lithium metal negative electrode by adjusting the concentration and coating amount of the PAA / fluoride or PAA / sulfide dispersion. The greater the concentration and the more coating, the thicker the protective layer obtained. The preparation method is simple and can be applied on a large scale.
[0024] (3) The lithium metal negative electrode provided by the present invention can effectively solve the problems of low cycle efficiency and dendrite growth of existing negative electrodes and their batteries. The battery using the composite lithium negative electrode has a longer cycle life than the battery using unprotected metal lithium negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic diagram of the process for preparing a lithium metal composite negative electrode provided by the present invention;
[0026] Figure 2 This is an optical photograph of the lithium metal composite negative electrode provided by the present invention;
[0027] Figure 3 is the full battery cycle curve using the lithium metal composite negative electrode in Example 1;
[0028] Figure 4 This is the full battery cycle curve using an unprotected lithium metal negative electrode in Comparative Example 1. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0030] The present invention provides a lithium metal composite negative electrode, characterized in that it comprises lithium metal and a lithium metal surface protective layer, wherein:
[0031] The lithium metal surface protection layer comprises an outer polymer elastic layer and an inner inorganic lithium-containing compound layer;
[0032] The outer polymer elastic layer is a Li-PAA layer, and the inner inorganic lithium-containing compound layer is a LiF or Li2S layer;
[0033] The inner inorganic lithium-containing compound layer is generated by a self-electrochemical reaction between lithium metal and fluoride or sulfide under the action of an electrolyte.
[0034] The present invention also provides a method for preparing the above-mentioned lithium metal secondary battery, characterized in that it comprises the following steps:
[0035] S1. In a dry air atmosphere, a dispersion of PAA / fluoride or PAA / sulfide is uniformly coated on the surface of lithium metal and dried in a blast oven. The adhesion property of PAA and the spontaneous reaction with lithium metal form a strong Li-PAA elastic protective layer. During the blast drying process, the contact portion of the fluoride or sulfide in the protective layer with the lithium metal undergoes a replacement reaction, a small amount of LiF or Li2S is generated inside the protective layer, and a surface protective layer of an outer Li-PAA layer and an inner small amount of LiF or Li2S layer is initially generated on the surface of the lithium metal, thereby obtaining a Li-PAA / fluoride / Li negative electrode or a Li-PAA / sulfide / Li negative electrode;
[0036] Preferably, the fluoride is any one of carbon fluoride, copper fluoride, magnesium fluoride, silver fluoride, cobalt fluoride and iron fluoride; the sulfide is any one of iron disulfide, copper sulfide, cobalt sulfide and chalcopyrite.
[0037] Preferably, the dispersion solvent is N-methylpyrrolidone.
[0038] Preferably, in the dispersion, the concentration of PAA is in the range of 0.1 wt% to 0.8 wt%, and the concentration of fluoride or sulfide is in the range of 0.1 wt% to 10 wt%.
[0039] Preferably, the coating amount of the dispersion on the surface of the lithium metal is in the range of 0.005-0.5 mL / cm 2 .
[0040] Preferably, the operating temperature of the blast oven is 50-80°C;
[0041] S2, assembling a Li-PAA / fluoride / Li negative electrode or a Li-PAA / sulfide / Li negative electrode and a high-capacity positive electrode into a battery and filling the corresponding electrolyte and then standing;
[0042] Preferably, the high-capacity positive electrode is any one of elemental sulfur, sulfided polyacrylonitrile, lithium-rich manganese-based, high-nickel ternary, and lithium cobalt oxide.
[0043] Preferably, the standing time is 6-24h.
[0044] S3. Utilize the further spontaneous electrochemical reaction between lithium metal and fluoride or sulfide under the action of electrolyte to completely convert the fluoride or sulfide in the surface protective layer into LiF or Li2S, generate a double-layer surface protective layer with an outer Li-PAA layer and an inner LiF or Li2S layer, and obtain a Li-PAA / LiF / Li negative electrode or a Li-PAA / Li2S / Li negative electrode, that is, a lithium metal composite negative electrode.
[0045] Preferably, the thickness of the surface protection layer in the lithium metal composite negative electrode is 100 nm-2 μm.
[0046] The present invention also provides a lithium metal secondary battery, characterized in that it comprises a negative electrode, a positive electrode, and an electrolyte, wherein the negative electrode is the above-mentioned lithium metal composite negative electrode or a lithium metal composite negative electrode prepared by the above-mentioned preparation method.
[0047] Examples
[0048] Example 1
[0049] (1) preparing a PAA / fluorocarbon NMP dispersion in a dry air atmosphere, wherein the PAA concentration is 0.1 wt % and the fluorocarbon concentration is 0.1 wt %;
[0050] (2) The coating amount of PAA / fluorinated carbon NMP dispersion on the lithium metal surface is 0.005 mL / cm 2 ;
[0051] (3) placing the lithium metal anode coated with PAA / fluorinated carbon in a 60° C. forced air oven for 1 h;
[0052] (4) A ternary high nickel (S85E) positive electrode, a celgard2320 separator, and an interface protected lithium metal negative electrode were assembled into a battery, and 1M LiPF6 / EC+EMC electrolyte was added and allowed to stand for 6 hours. Finally, the thickness of the metal lithium surface protection layer in the composite lithium metal negative electrode was 100 nm.
[0053] The battery capacity is 5.5Ah, and the capacity retention rate is 86.8% after 100 cycles in the voltage range of 2.8-4.4V, and the efficiency is still as high as 99.1%. The full battery cycle curve of this battery is as follows Figure 3 shown.
[0054] Example 2
[0055] (1) preparing a PAA / fluorocarbon NMP dispersion in a dry air atmosphere, wherein the PAA concentration is 0.5 wt % and the fluorocarbon concentration is 0.5 wt %;
[0056] (2) The coating amount of PAA / fluorinated carbon NMP dispersion on the lithium metal surface is 0.01 mL / cm 2 ;
[0057] (3) placing the lithium metal anode coated with PAA / fluorinated carbon in a 60° C. forced air oven for 1 h;
[0058] (4) A sulfur positive electrode, a celgard 2320 separator, and an interface-protected lithium metal negative electrode were assembled into a battery, and 1 M LiTFSI / dol+DME electrolyte was added and allowed to stand for 8 h. Finally, the thickness of the metal lithium surface protection layer in the composite lithium metal negative electrode was 200 nm.
[0059] The battery capacity is 3Ah, and the capacity retention rate is 70.5% after 100 cycles in the voltage range of 1.5-2.8V.
[0060] Example 3
[0061] (1) preparing a PAA / iron disulfide NMP dispersion in a dry air atmosphere, wherein the PAA concentration is 0.2 wt % and the iron disulfide concentration is 0.5 wt %;
[0062] (2) The coating amount of PAA / iron disulfide NMP dispersion on the lithium metal surface is 0.01 mL / cm 2 ;
[0063] (3) placing the lithium metal anode coated with PAA / iron disulfide in a forced air oven at 60° C. for 2 h;
[0064] (4) A ternary high nickel (S85E) positive electrode, a celgard2320 separator, and an interface protected lithium metal negative electrode were assembled into a battery, and 1M LiPF6 / EC+EMC electrolyte was added and allowed to stand for 8 hours. Finally, the thickness of the metal lithium surface protection layer in the composite lithium metal negative electrode was 300 nm.
[0065] The battery capacity is 5.3Ah, and the capacity retention rate is 87.6% after 100 cycles in the voltage range of 2.8-4.4V.
[0066] Example 4
[0067] (1) preparing a PAA / silver fluoride NMP dispersion in a dry air atmosphere, wherein the PAA concentration is 0.5 wt % and the silver fluoride concentration is 1 wt %;
[0068] (2) The coating amount of PAA / silver fluoride NMP dispersion on the lithium metal surface is 0.02 mL / cm 2 ;
[0069] (3) placing the lithium metal anode coated with PAA / silver fluoride in a 60° C. forced air oven for 1.5 h;
[0070] (4) A lithium-rich manganese-based positive electrode, a celgard2320 separator, and an interface-protected lithium metal negative electrode were assembled into a battery, and 1M LiPF6 / EC+EMC electrolyte was added and allowed to stand for 12 hours. Finally, the thickness of the metal lithium surface protection layer in the composite lithium metal negative electrode was 500 nm.
[0071] The battery capacity is 6Ah, and the capacity retention rate is 77.6% after 100 cycles in the voltage range of 2.0-4.8V.
[0072] Comparative Example 1
[0073] (1) In a dry air atmosphere, a ternary high nickel (S85E) positive electrode, a celgard 2320 separator, and a lithium metal negative electrode without interface protection were assembled into a battery, and 1M LiPF6 / EC+EMC electrolyte was added and allowed to stand for 6 hours.
[0074] The battery capacity is 5.7Ah, and the capacity retention rate after 60 cycles is 71.5%. The efficiency drops to 95.1% at the 60th cycle. The full battery cycle curve of this battery is as follows: Figure 4 shown.
[0075] The lithium metal surface protection layer provided by the present invention, the outer Li-PAA elastic protection layer can adapt to and buffer the large volume change of the lithium metal negative electrode during the charging and discharging process, the inner LiF or Li2S inorganic lithium-containing compound layer is conducive to the rapid transmission of lithium ions, and has a high Young's modulus, can inhibit the formation of lithium metal dendrites, and greatly extend the cycle life of the lithium metal secondary battery. The preparation method of the lithium metal composite negative electrode disclosed by the present invention is simple and has low equipment requirements.
[0076] The contents not described in detail in this specification belong to the prior art known to those skilled in the art. It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.
Claims
1. A lithium metal composite negative electrode, characterized in that: It includes lithium metal and a lithium metal surface protection layer, wherein: The lithium metal surface protection layer comprises an outer polymer elastic layer and an inner inorganic lithium-containing compound layer; The outer polymer elastic layer is a Li-PAA layer, and the inner inorganic lithium-containing compound layer is a LiF or Li2S layer; The inner inorganic lithium-containing compound layer is generated by a self-electrochemical reaction between lithium metal and fluoride or sulfide under the action of an electrolyte.
2. The method for preparing a lithium metal composite negative electrode according to claim 1, characterized in that: It includes the following steps: S1. In a dry air atmosphere, a dispersion of PAA / fluoride or PAA / sulfide is uniformly coated on the surface of lithium metal and dried in a blast oven to preliminarily form a surface protective layer of an outer Li-PAA layer and an inner small amount of LiF or Li2S layer on the surface of lithium metal to obtain a Li-PAA / fluoride / Li negative electrode or a Li-PAA / sulfide / Li negative electrode; S2, assembling a Li-PAA / fluoride / Li negative electrode or a Li-PAA / sulfide / Li negative electrode and a high-capacity positive electrode into a battery and filling the corresponding electrolyte and then standing; S3. Utilize the further spontaneous electrochemical reaction between lithium metal and fluoride or sulfide under the action of electrolyte to completely convert the fluoride or sulfide in the surface protective layer into LiF or Li2S, generate a double-layer surface protective layer with an outer Li-PAA layer and an inner LiF or Li2S layer, and obtain a Li-PAA / LiF / Li negative electrode or a Li-PAA / Li2S / Li negative electrode, that is, a lithium metal composite negative electrode.
3. The preparation method according to claim 2, characterized in that: The fluoride is any one of carbon fluoride, copper fluoride, magnesium fluoride, silver fluoride, cobalt fluoride and iron fluoride; The sulfide is any one of iron disulfide, copper sulfide, cobalt sulfide and chalcopyrite.
4. The preparation method according to claim 2, characterized in that: The thickness of the surface protection layer in the lithium metal composite negative electrode is 100nm-2μm.
5. The preparation method according to claim 2, characterized in that: The high-capacity positive electrode is any one of elemental sulfur, sulfided polyacrylonitrile, lithium-rich manganese-based, high-nickel ternary, and lithium cobalt oxide.
6. The preparation method according to claim 2, characterized in that: The dispersion solvent is N-methylpyrrolidone.
7. The preparation method according to claim 2, characterized in that: In the dispersion, the concentration of PAA is in the range of 0.1 wt% to 0.8 wt%, and the concentration of fluoride or sulfide is in the range of 0.1 wt% to 10 wt%.
8. The preparation method according to claim 2, characterized in that: The coating amount of the dispersion on the surface of the metal lithium is in the range of 0.005-0.5 mL / cm 2 .
9. The preparation method according to claim 2, characterized in that: The operating temperature of the blast oven is 50-80° C.; the standing time is 6-24 hours.
10. A lithium metal secondary battery, characterized in that: It comprises a negative electrode, a positive electrode and an electrolyte. The negative electrode is the lithium metal composite negative electrode according to claim 1, or the lithium metal composite negative electrode prepared by the preparation method according to any one of claims 2 to 9.
Citation Information
Patent Citations
Lithium metal battery lithium negative electrode surface modification method, and lithium metal battery
CN108448058A
Lithium anode with inorganic protective coating and preparation method thereof
CN108565398A
Preparation and application of lithium metal anode with composite film
CN110190243A
Cited By
Lithium negative electrode, preparation method thereof and battery
CN121149161A